RFID-Based Vehicle Access and Monitoring System - MASRI, NUR NADHIRAH; Ab. Aziz, Ruhaya (Applied Information Technology And Computer Science, 2025)
Radio Frequency Identification (RFID) technology uses electromagnetic fields to identify and track objects, making it an effective tool for security. This project aims to develop an RFID-Based Vehicle Access and Monitoring System to address inefficiencies, human errors, and security risks in Universiti Tun Hussein Onn Malaysia's (UTHM) current manual vehicle access system. The system is designed using an object-oriented approach and follows the prototyping model to iteratively develop the solution. It integrates RFID tags to automate vehicle access and provide real-time monitoring. The implementation includes vehicle entry points on UTHM's main campus, with a focus on operational efficiency and increased security. The expected results include reduced human error, shorter wait times at entry points, and improved data accuracy for security purposes. This study shows how automation can make campus environments safer and more efficient, and it proposes additional improvements for future systems, such as integrating statistical analysis.